Promotion or Prevention Messaging?: A Field Study on What Works When You Still Have to Work - Roczniewska, Marta Anna; Higgins, E. Tory (Frontiers in Psychology, 2018)
This article addresses the timely subject of the reactions towards a Sunday trade ban in Poland. The law introduced in March 2018 created a division among service employees: (1) those who used to work on Sundays before the law and now enjoy work-free Sundays, and (2) those who used to work and still have to work on Sundays. Although the objective circumstances did not change for this latter group, their current status quo (0) now had a new better state (+1) as a contrast reference point. Hence, this group experiences a non-gain rather than a loss. Using the framework of regulatory focus (Higgins, 1997) and regulatory fit (Higgins, 2000) theories, we predicted that the individuals in the non-gain condition would process a promotion (vs. prevention)-framed message more fluently. We also predicted that processing fluency would enhance fairness perceptions among these employees. To test these predictions, we conducted a field experiment, manipulating message framing among two groups of service employees: those who gained and those who did not gain as a result the Sunday trade ban. Analysis of variance revealed that employees in a non-gain promotion framing condition processed the message more fluently than those in a prevention framing condition. A moderated mediation analysis also showed that the processing fluency resulting from fit created higher fairness perceptions. Repercussions for communicating about organizational non-gain changes are discussed.